The Impact of the Different Numerical Density of the Two-Spot Dream Roles Tetranychus Urticae Koch in His Predator Life) Mulsant Gilvifrons Stethorus. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
A Laboratory study was conducted to show the different numerical stage density for mite of two spots tetranychus  urticae on the life cycle of stethorus gilvifrons at 30cº and a relative humidity 70±5%, the results showed that the differences in numerous density 5,10,20,40,80 of mite havens high effect on the life cycle, at density 80 mites the larva and the adult reached high level of development and production, while the numerous density 5 is the lowest which can be the larva continued it is development.The results showed that the increasing in two spots mites means increasing in rate daily consume in each larva in stare it showed that the density of 80 mites the average rate of consumption for four larva in stare 23.3, 28.3, 37, 44.6 respectively, while showed the minimum consumption at density 5mites reach 4.0,5,5,5 mites respectively, and the shortest periods for larva instars development at density 80mites,1.6 ,1,1.3,2.0 day, while the longest period for development larva in stare at density  5mites reach 2, 3,3.3,6.6day respectively. The result showed that the eggs which are laying by the female of predator, 65-140 eggs at rate of 100 eggs at density of 80 mite, while the range is 2 eggs at 10 numerous density effected on the age of adult insect for both male and female, the maximum rate for the adult 44.6 , 35.0 day at numerous density 80 mite respectively and the minimum rate 8.0, 3.3 day at density 5 mites.